A Women entrepreneurial spirit and success: entrepreneurial start-up programme - Noorliza, K. (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to identify factors that can cultivate women entrepreneurial spirit and/or entrepreneurial orientation through the execution of entrepreneurial start-up program in the context of local community. This paper is a qualitative analysis of action research on a new farming entrepreneurial start-up program designing for women entrepreneurs in rural community context, based on observations, photos and interviews. The results reveal that the entrepreneurial start-up program has a positive effect on entrepreneurial spirit/orientation and entrepreneurial success. The emerging of entrepreneurial support system helps in the development of women entrepreneurs to start-up and develop their business. Sufficient resources and supports; entrepreneurial intrinsic values and business opportunities are essential for the entrepreneurial success. This study has been made in a rural community context, which can be adapted to different sectors for future research and applications therefore it contributes to the organizational and entrepreneurial in general through new approaches to entrepreneurship model that fosters healthy women entrepreneurial spirit/orientation. Government should aware that entrepreneurial start-up program can nurture and inspire the healthy entrepreneurial spirit/orientation that leads to entrepreneurial success. The study provides directions to policy makers and academicians to focus on innovative development programmes for women entrepreneurs. The study predominantly focuses on practice rather than theory, and establishes an entrepreneurship model for nurturing women entrepreneurial spirit and/or entrepreneurial orientation through entrepreneurial start-up programme.